1999
DOI: 10.1152/ajprenal.1999.277.6.f882
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide induces vasodilation and nitric oxide release but suppresses endothelial NOS

Abstract: The vascular effects of carbon monoxide (CO) resemble those of nitric oxide (NO), but it is unknown whether the two messengers converge or exhibit reciprocal feedback regulation. These questions were examined in microdissected perfused renal resistance arteries (RRA) studied using NO-sensitive microelectrodes. Perfusion of RRA with buffers containing increasing concentrations of CO resulted in a biphasic release of NO. The NO response peaked at 100 nM CO and then declined to virtually zero at 10 microM. When a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
198
3
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(217 citation statements)
references
References 43 publications
12
198
3
4
Order By: Relevance
“…The next possible mechanism is down-regulation of iNOS expression by degradation of heme, as an essential cofactor for iNOS protein assembly and activity. Finally, CO, the other product of HO-1, has a protective role and inhibits NO synthase activity (42) or JNK activity and suppresses pro-inflammatory cytokine production (43). In this study, we found that both HO-1 induction and a CO-releasing compound, [Ru(CO) 3 Cl 2 ] 2 , activated ERK5/PPAR␦.…”
Section: Discussionmentioning
confidence: 53%
“…The next possible mechanism is down-regulation of iNOS expression by degradation of heme, as an essential cofactor for iNOS protein assembly and activity. Finally, CO, the other product of HO-1, has a protective role and inhibits NO synthase activity (42) or JNK activity and suppresses pro-inflammatory cytokine production (43). In this study, we found that both HO-1 induction and a CO-releasing compound, [Ru(CO) 3 Cl 2 ] 2 , activated ERK5/PPAR␦.…”
Section: Discussionmentioning
confidence: 53%
“…Because cardiac fibrosis is difficult to study in human patients, other than its therapeutic relevance, our findings may have diagnostic implications, because the DOCA-salt model displays distinct fibrotic characteristics. 6 Although the HO system is cytoprotective, 9 -11 some reports indicate that carbon monoxide may interfere with NO-induced vasodilation, 35 causing endothelium-dependent vasoconstriction. 36 These studies suggest that carbon monoxide may have a biphasic effect, and, therefore, the specific conditions under which different experiments are done may be critical to the observed effect.…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency of HO in a human has been described (Yachie et al, 1999) and, as with the HO-1 null mutant mice (Poss and Tonegawa, 1997), there was growth restriction. An effect of HO-1 on cell proliferation (Clark et al, 1997;Deramaudt et al, 1998), vasodilatation (Thorup et al, 1999;Zhang et al, 2001), and postnatal growth (Sabaawy et al, 2001) has been documented. Gene transfer of hHO-1 into coronary endothelial cells promoted angiogenesis (Deramaudt et al, 1998) and inhibitors of HO increased placental resistance (Lyall et al, 2000).…”
Section: Discussionmentioning
confidence: 99%